THE ROLE OF LIQUIDITY RISK, INTEREST RATE RISK, AND CREDIT RISK IN INFLUENCING THE FINANCIAL PERFORMANCE OF INDONESIAN BANKS - Vina Ayu Nur Septyana; Rani Lokonta Sari Sembiring; Farah Margaretha Leon (Accounting Profession Journal (APAJI), 2025)
This study aims to examine the effect of liquidity risk, credit risk, loan-to-deposit ratio (LDR), and bank size on the financial performance of banks in Indonesia listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The sample consists of 41 banks with a total of 205 annual observations. The analysis method used is panel data regression with the Random Effect Model approach using Eviews 9.0 software. The results showed that liquidity risk, LDR, and bank size had a significant positive effect on financial performance proxied by Return on Assets (ROA), while credit risk had a significant negative effect on ROA. These findings indicate that liquidity management, efficiency in lending, and the scale of bank assets are important factors in increasing bank profitability.